2016
DOI: 10.1177/183693911604100114
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a School Readiness Program on the Language and Phonological Awareness Skills of Preschool Children in Rural Areas of South Africa

Abstract: MANY CHILDREN IN DEVELOPING countries are exposed to multiple risks for poor development due to poverty and associated poor health and nutrition. These factors, as well as insufficient knowledge of the prerequisites for emergent literacy and school readiness on the side of parents and practitioners, may contribute to the weak reading achievement of learners. The question underlying this research was formulated as follows: Will the phonological awareness of preschool children improve after the application of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…2009;Boyer, 2010;Wilkowski, 2012). İlgili alanyazında uyaklı sarkıların ve siirlerin söylenmesinin, aynı sesle basļayan sözcükleri kullanarak oyunlar oynanmasının, nesnelerin ilk ve son sesine dikkat ederek gruplama yapmaya yönelik uygulamaların fonolojik farkındalık becerilerini gelisţirmede etkili olduğu belirtilmektedir (De Witt & Lessing, 2016;Flett & Conderman, 2002;Paulson, 2004). Bu araştırmada da benzer nitelikte uygulamalara yer verilmiş ve bu uygulamalar aracılığı ile sesleri tanıma, ses birimlerini fark etme, harfler ve sesler arasında bağlantı kurma, sözcükleri hecelerine doğru ayırma becerileri desteklenmiştir.…”
Section: Etik Beyanunclassified
See 1 more Smart Citation
“…2009;Boyer, 2010;Wilkowski, 2012). İlgili alanyazında uyaklı sarkıların ve siirlerin söylenmesinin, aynı sesle basļayan sözcükleri kullanarak oyunlar oynanmasının, nesnelerin ilk ve son sesine dikkat ederek gruplama yapmaya yönelik uygulamaların fonolojik farkındalık becerilerini gelisţirmede etkili olduğu belirtilmektedir (De Witt & Lessing, 2016;Flett & Conderman, 2002;Paulson, 2004). Bu araştırmada da benzer nitelikte uygulamalara yer verilmiş ve bu uygulamalar aracılığı ile sesleri tanıma, ses birimlerini fark etme, harfler ve sesler arasında bağlantı kurma, sözcükleri hecelerine doğru ayırma becerileri desteklenmiştir.…”
Section: Etik Beyanunclassified
“…Many studies have found that teaching phonological awareness enables students to acquire phonological awareness skills (Al Otaiba et al 2009;Boyer, 2010;Wilkowski, 2012). When the relevant literature was reviewed, it was found that singing rhymed songs and poems, playing word games that start with the same sound, and grouping objects by the first and last sound of their name were found to be effective in promoting phonological awareness (De Witt & Lessing, 2016;Flett & Conderman, 2002;Paulson, 2004). In this study, similar practices were included and with the help of them, the skills as recognizing sounds, recognizing phonemes, making connections between letters and sounds, and separating words into syllables were supported.…”
Section: Extended Summarymentioning
confidence: 99%
“…Early literacy refers to the knowledge of the relation between language, phonological and phonemic awareness, knowledge of the alphabet and an understanding of common print concepts related to reading and writing that a young child should obtain before starting with the formal reading process (Castro & Barrera, 2019). However, it is not only about the ability to identify letters, numbers and shapes but also implies a set of skills, knowledge and attitudes of which the main components include an awareness of language, listening, oral communication and writing skills (Shrier, 2013;De Witt & Lessing, 2016). Elements such as attention, vocabulary, phonological and phonemic awareness, knowledge of the alphabet, understanding of common print concepts, drawing skills and several perceptual competencies go hand in hand Both auditory and visual perception as early literacy skills are important in the reading process as various sensory modalities are activated to enhance understanding (comprehension) when reading a passage.…”
Section: Early Literacymentioning
confidence: 99%
“…The mastering of form consistency enables the child to recognise the shape of letters and words in the reading process. Form consistency relies on the cognitive ability to recognise and manipulate forms irrespective of size, form or direction and to visualise an outcome when using them (De Witt & Lessing, 2016;Kaiser & Hemmeter, 2014). To successfully complete an activity on form consistency requires relevant perceptual skills and concepts and depends on cognitive processes, which entail the EF.…”
Section: Form Consistencymentioning
confidence: 99%
See 1 more Smart Citation